Statistical and Interpretative Analyses for Testing Customer Trust Questionnaires on IT Governance - Resad, Setyadi; Aedah, Abd Rahman; A'ang, Subiyakto (2019)
The purpose of the research is testing customer trust questionnaires on ITG trust through statistical and interpretative analyses. ITG questionnaire data obtained will be analyzed using SMART PLS 3.28 that included testing a formative construction and causal modeling capabilities. The result of this research is interpretive data analyses to confirm the results of the statistical analysis in the testing questionnaire of ITG trust. The results of this study are expected to be a literature or reference for stakeholder in school who are running their ITG and actually can give other solution for ITG in high school institution (HSI). The school with the media-based on ITG trust model has Effectiveness, Productivity, Efficiency, and increasing the management quality in a sustainable manner and resulting high performance achievement.